Penguatan Mental Health Awareness Melalui Forgiveness Therapy dan Resilience Training bagi Warga Binaan Perempuan di Lembaga Pemasyarakatan - Nur Fadhilah Umar; Arifin Manggau; Muh. Nur Alamsyah; Febrianto Syam; Asri Nur Aina (Lembaga Pengembangan Kinerja Dosen, 2025)
Female prisoners at Class IIA Gowa Correctional Facility face complex psychological challenges, such as guilt, trauma, and social isolation, which have the potential to reduce awareness of the importance of mental health. This community service program aims to increase mental health awareness through an educational and therapeutic approach based on Forgiveness Therapy and Resilience Training. Activities are carried out through three stages: problem identification and coordination with the prison, intervention implementation, and evaluation of results. Participatory methods are used to build active involvement of prisoners, with techniques such as group discussions, positive affirmations, Butterfly Hug, and emotional journal writing. The results showed an increase in participants' understanding of mental health, ability to forgive themselves, and resilience in dealing with life pressures. In conclusion, this intervention is effective in supporting the emotional recovery of prisoners and has the potential to become a model of psychosocial services that can be replicated in other correctional institutions.